A Taxonomic Review of the Australian Butterfly Ray Gymnura australis (Ramsay & Ogilby, 1886) and Other Members of the family Gymnuridae (Order Rajiformes) from the Indo-West Pacific - Jacobsen, Ian P.; Bennett, Mike B. (Zootaxa, 2009)
The taxonomy of G. australis was examined as part of a wider review of Indo-West Pacific Gymnuridae species. The study revealed two distinct morphological variants: G. australis var. eastern Australia and G. australis var. northern Australia. Gymnrua australis var. eastern Australia has ≤ 3 complete or partially-complete white tail-bands and may or may not have a dorsal fin. Gymnura australis var. northern Australia has a longer tail region, always possesses a dorsal fin and has ≥ 4 predominantly complete white tail-bands. Morphological and genetic comparisons indicate the observed differences were intraspecific (1.22% genetic gap difference). Wider morphometric comparisons between Indo-West Pacific gymnurids, revealed species differ principally in tail morphology. Dorsal-fin development in G. zonura also varied intraspecifically. Results obtained from the study, help clarify the taxonomic status of the family and provide strong evidence that all Gymnuridae species belong to a single genus Gymnura, with Aetoplatea subsequently defined as a junior synonym.